1990
DOI: 10.1002/aja.1001890310
|View full text |Cite
|
Sign up to set email alerts
|

Prenatal development of the human nucleus ambiguus during the embryonic and early fetal periods

Abstract: The ontogenetic development of the nucleus ambiguus was studied in a series of human embryos and fetuses ranging from 3 to 12.5 weeks of menstrual age (4 to 66 mm crown-rump length). They were prepared by Nissl and silver methods. Nucleus ambiguus neuroblasts, whose neurites extend towards and into the IXth and rostral Xth nerve roots, appear in the medial motor column of 4-6-week-old embryos (4.25-11 mm). These cells then migrate laterally (6.5 weeks, 14 mm) to a position near the dorsal motor nucleus of X. A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
12
0
1

Year Published

1993
1993
2014
2014

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 117 publications
1
12
0
1
Order By: Relevance
“…On the other hand, our results support the hypothesis raised for humans by Jacobs (1970) and Brown (1990) that those neuroblasts that first complete their differentiation and cease migration are the first to become functional. The migration of facial neuroblasts in the midline neuroepithelium occurs along a diagonal axis from the rostral dorsomedial to the caudal ventrolateral position (Jacobs, 1970;Auclair et al 1996;Swanson et al 1999).…”
Section: Relationship Between Cytoarchitecture Musculotopic Organizasupporting
confidence: 91%
“…On the other hand, our results support the hypothesis raised for humans by Jacobs (1970) and Brown (1990) that those neuroblasts that first complete their differentiation and cease migration are the first to become functional. The migration of facial neuroblasts in the midline neuroepithelium occurs along a diagonal axis from the rostral dorsomedial to the caudal ventrolateral position (Jacobs, 1970;Auclair et al 1996;Swanson et al 1999).…”
Section: Relationship Between Cytoarchitecture Musculotopic Organizasupporting
confidence: 91%
“…As such, these results indicate organization of a distinct nucleus between El5 and E17, and maturation and further differentiation of the neuroblasts through E19. This overall temporospatial pattern observed in the rat NA (i.e., initial appearance of NA rostrally followed by organization throughout the caudal extent followed by maturation of motoneurons) has also been noted in a histological study of the developing human NA (Brown, 1990). Furthermore, our observed maturation of motoneurons in NA coincides with critical periods in the development of rat muscle fibers (Rubinstein and Kelly, 1981) and, as such, provides a temporal basis for coordinated developmental sequences between motoneurons and their target muscles (Ross et al, 1987).…”
Section: Discussionmentioning
confidence: 79%
“…Labeling of migrating motoneurons was considered possible based on three observations: (1) Motor axons in the mature NA initially project dorsally before ''looping'' ventrolaterally to leave the brainstem, thus implying migration after axogenesis (Kalia and Mesulam. 1980;GrClot et al, 1989); (2) histological studies of developing neuroblasts, including those in NA, observed axonal projections leaving the central nervous system prior to and during the period of migration (Levi- Montalcini, 1964;Heaton et al, 1978;Brown, 1990); and (3) neural tracing studies have previously been shown to label apparently migrating neurons (Heaton and Moody, 1980;Lumsden and Keynes, 1989). These findings suggested that application of tracer to URT nerves, just distal to their exit from the brainstem, would label any motoneurons still migrating to the ventrolateral NA during the period of MCD.…”
Section: Neuroanatomical Tracing Proceduresmentioning
confidence: 99%
“…The target of early NA axons is likely the esophagus because the NA innervates the esophagus but not the stomach or other abdominal viscera in mature rats (Bieger and Hopkins, 1987;Rinaman and Miselis, 1987;Altschuler, Bao, and Miselis, 199 1;Altschuler, Ferenci, Lynn, and Miselis, 199 1 ) . An early lateral migration of NA motor neurons has also been described in human fetuses (Brown, 1990) and appears to be a developmental characteristic of motor nuclei that supply branchiomeric muscles (Heaton and Moody, 1980), such as those within the esophagus. These NA motor neurons may already receive central synaptic inputs at E13, as motor neuron dendritic growth has been shown to occur synchronously with the formation of axodendritic synapses (Vaughn et a]., 1974).…”
Section: Na and Dmvmentioning
confidence: 86%
“…As in the adult, most NA axons arch dorsally and then turn ventrolaterally to join the heavily labeled bundle of exiting DMV motor axons. This axonal arching pattern indicates that NA motor neurons first migrate radially, sending their axons out of the same region of the ventrolateral medulla where DMV axons exit, but then the NA somata subsequently migrate ventromedially (see also Brown, 1990).…”
Section: E14mentioning
confidence: 93%